2022
DOI: 10.1371/journal.pmed.1003940
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reengage people living with HIV who are lost to follow-up from HIV treatment programs: A systematic review and meta-analysis

Abstract: Background Optimizing services to facilitate engagement and retention in care of people living with HIV (PLWH) on antiretroviral therapies (ARTs) is critical to decrease HIV-related morbidity and mortality and HIV transmission. We systematically reviewed the literature for the effectiveness of implementation strategies to reestablish and subsequently retain clinical contact, improve viral load suppression, and reduce mortality among patients who had been lost to follow-up (LTFU) from HIV services. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…23 Reengagement strategies are critical, as shown in a meta-analysis that highlighted that active reengagement strategies increased patient return to care by 20% as compared with the standard of care. 34 The interface between public health departments and clinics can provide a forum to address D2C opportunities identified in the HCV viral clearance cascade. For example, we found that people with HIV transmission categories other than PWID (eg, MSM, heterosexual) were significantly less likely to receive HCV viral testing than PWID.…”
Section: Discussionmentioning
confidence: 99%
“…23 Reengagement strategies are critical, as shown in a meta-analysis that highlighted that active reengagement strategies increased patient return to care by 20% as compared with the standard of care. 34 The interface between public health departments and clinics can provide a forum to address D2C opportunities identified in the HCV viral clearance cascade. For example, we found that people with HIV transmission categories other than PWID (eg, MSM, heterosexual) were significantly less likely to receive HCV viral testing than PWID.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Participants that were not re-engaged were more likely to have a history of drug use, to have tested in the pre-DAA era, and were less likely to have a prior specialist evaluation. (20) Other patient tracing and re-engagement studies concerned with HIV care have had varying results from using a combination of methods to re-engage patients who are lost to follow-up, (21)(22)(23) including text messaging, (24,25) telephone calls, (26-28) email, (22) letters,( 29) and physical tracing. (30)(31)(32) Newly treated individuals were a mixture of individuals already known to the ODN, and individuals not known, who might have been unaware of their infection, aware of their infection but not engaged with healthcare services, and/or unaware of the emergence of new, better tolerated and more effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed specification and characterization of primary implementation strategies and co-strategies was not robust across studies included in reviews. As an example, in a review of re-engagement in care strategies—actors (those who conducted tracing efforts) and actions (tracing activities performed) were generally well specified; however, other implementation characteristics, such as the dose (frequency and intensity of contact attempts) and temporality (time when tracing was initiated in relation to last visit or appointment) and the action target (how a “lost” patient was defined and how the tracing sought to re-engage them) were less clear [ 12 , 17 ]. In addition, descriptions of adaptations made during implementation were infrequent.…”
Section: Suboptimal Characterization Of Strategies Adaptations Mechan...mentioning
confidence: 99%